Effects of Rotating Rice with Upland Crops and Adding Organic Amendments, and of Related Soil Quality on Rice Yield in the Vietnamese Mekong Delta - Nguyen Van Qui; Le Van Khoa; Nguyen Minh Phuong; Duong Minh Vien; Tran Van Dung; Tran Ba Linh; Tran Huynh Khanh; Bui Trieu Thuong; Vo Thi Thu Tran; Nguyen Khoi Nghia; Tran Minh Tien; Emmanuel Abatih; et al. (Agronomy, 2024)
In the Vietnamese Mekong Delta, soil quality and crop yield are steadily declining under rice monocultures with three crops per year. The objective of this study was to evaluate the medium-term effects of rotating rice with upland crops and adding organic amendments on rice yield, and to relate this to soil quality. A field trial with split-plot design including two factors and three replicates was carried out from 2017 to 2020, over the course of nine consecutive cropping seasons. Crop rotations and organic amendments were applied as main-plot and subplot factors, respectively. The rotations were (1) rice–rice–rice (R–R–R), (2) soybean–rice–rice (So–R–R), and (3) sesame–rice–rice (Se–R–R), while organic amendment treatments included (i) no amendment (NO-AM), (ii) compost of rice straw and cow manure (RS+CM), and (iii) sugarcane compost (SGC); the composts were applied at a rate of 2.0 t ha−1. The rotation cycle started with the so-called spring–summer (SS) season, followed by the summer–autumn (SA) season and ending with the winter–spring (WS) season. Rice yield significantly (p < 0.05) increased under organic amendments after nine growing seasons (2019–2020 WS), with an increment of 5.1% for RS+CM (7.07 ton/ha) and 6.1% for SGC (7.14 ton/ha). Contrary to our expectation, rotations with upland crops did not significantly increase rice yield. Rice yield significantly and positively correlated with an integrated soil quality index–SQI (r = 0.85) for the topsoil (0–15 cm), but not for the subsoil (15–30 cm). The increased availability of soil nutrients (Si and marginally also P) and improved soil physical properties probably induced by organic amendments, along with other soil properties under study, cumulatively attributed to enhanced rice yield. Repeated organic amendments thus becomes an effective management practice in improving soil quality under rice-based systems and could be applied to sustain rice yield in rice-producing regions with similar soil types and climatic conditions. Use of a SQI involving several soil quality indicators enables us to quantify the overall importance of soil fertility for rice yield versus other factors, and it provides an effective means of quantifying the integrated effect of improved management. Moreover, integrating a wide range of soil quality indicators in a SQI ensures its applicability across diverse settings, including different crop rotations and various soil types.